Pretreatment hematological markers predict clinical outcome in cancer patients receiving immune checkpoint inhibitors: A meta‐analysis. Issue 10 (27th August 2018) - Tan, Qiaoyun; Liu, Shuxia; Liang, Caixia; Han, Xiaohong; Shi, Yuankai
Abstract : Background: Immune checkpoint inhibitors (ICIs) have revolutionized the clinical treatment of multiple cancers. Recent studies revealed the potential prognostic value of the neutrophil to lymphocyte ratio (NLR) and platelet to lymphocyte ratio (PLR) in patients receiving ICIs; however, the results were inconsistent. We conducted a meta‐analysis to identify the prognostic significance of baseline NLR and PLR in cancer patients treated with ICIs. Methods: We conducted a thorough literature search of PubMed, Embase, and Cochrane databases for studies dealing with the prognostic impact of pretreatment NLR and/or PLR levels in cancer patients treated with ICIs. The clinical outcomes were progression‐free survival (PFS) and overall survival (OS). Hazard ratios (HRs) and 95% confidence intervals (CIs) were calculated, and sensitivity and subgroup analyses were performed to investigate heterogeneity. Results: Seventeen articles involving 2092 patients were included in the final analysis. The pooled HRs of PFS and OS for NLR were 1.81(95% CI 1.36–2.41) and 2.26 (95% CI 1.68–3.03), respectively, suggesting that patients with higher baseline NLRs had significantly poorer PFS and OS. Similar results were detected in sensitivity and subgroup analyses. However, no significant relevance was found between PLR and clinical endpoints in patients treated with ICIs (HR = 1.14, 95% CI 0.88–1.48 for PFS; HR = 1.35, 95% CI 0.86–2.12 for OS). Conclusion: These results indicate that high pretreatment NLR but not PLR level, as a routinely obtained hematological parameter, is a potential prognostic predictor for poor PFS and OS in cancer patients receiving ICIs.